Human resource management in health care : principles and practice - McConnell, Charles R. (Jones & Bartlett., 2021)
"This practical, hands-on book introduces human resources to those who are preparing to work in any area of health care or health service. Written for practitioners and students in all disciplines related to health, it covers important topics such as recruitment, training, termination, legal issues, labor unions, and more. Each chapter is introduced by a case study related to the material that follows. The case study is resolved at the conclusion of each chapter along with expert commentary and practical suggestions that can be used in the real world. Chapters also feature learning objectives, discussion points, and questions for review. Many examples and a number of sample forms and documents are included"--